(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
This paper analyzes cash flow management practices within the treasury of Uzbekistan, focusing on key strategies, operational challenges, and their impacts on financial stability. The study employs a mixed-methods approach, combining quantitative data analysis and qualitative interviews with treasury officials. Findings reveal critical insights into current practices and recommend optimizing cash flow management to enhance overall fiscal efficiency.